2014
DOI: 10.1063/1.4894825
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent failure mechanisms of nanocrystalline gold interconnect lines under general alternating current

Abstract: Thermal fatigue failure of metallization interconnect lines subjected to alternating currents (AC) is becoming a severe threat to the long-term reliability of micro/nanodevices with increasing electrical current density/power. Here, thermal fatigue failure behaviors and damage mechanisms of nanocrystalline Au interconnect lines on the silicon glass substrate have been investigated by applying general alternating currents (the pure alternating current coupled with a direct current (DC) component) with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Even for the case of no resistance variation at all, i.e. when the system is driven at current densities much lower than the EM current, there is an inevitable thermal fatigue loading generated by the alternating current which may lead to a premature breakdown of the device [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Even for the case of no resistance variation at all, i.e. when the system is driven at current densities much lower than the EM current, there is an inevitable thermal fatigue loading generated by the alternating current which may lead to a premature breakdown of the device [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to structural applications of the electrohealing, the self-healing approach is also being studied for solders, submicron aluminum and nanocrystalline gold interconnectors to solve the electromigration problems, the significance of which increases notably as the size of integrated circuit decreases [57][58][59][60][61]. Electrical testing showed that cracks formed due to electromigration can disappear upon the application of a high-density current of the right duration.…”
Section: Electro-healingmentioning
confidence: 99%
“…The combination of SM and TF may cause cracks, voids, and hillocks to form in the thin films, leading to a deterioration of the electrical conductivity. 7,8 TF failure of metallization interconnect lines subjected to alternating currents has been reported, 912 and the damage and failure were caused the deformation-induced motion of dislocations to the grain boundaries. However, TF in the printed Ag film has not been investigated.…”
Section: Introductionmentioning
confidence: 99%